Watch Your Language: Translating Science-Based Research for Public Consumption - Susan Grantham; Tracy Irani (Journal of Applied Communications, 2004)
Communications professionals involved with agriculture and natural resources have a stake in developing a scientifically literate public. Much of the terminology used to discuss science-based research issues has its foundation in Latin and Greek. Research has demonstrated that scientific literacy is directly affected by the educational process. However, limited work has been done about the relationship between scientific literacy skills and coursework in the sciences and foreign language. The purpose of this research was to explore this relationship. A descriptive survey was administered to a sample of undergraduate students at a large southeastern university. The survey was designed to assess the respondents’ ability to define a set of scientific terms as a function of the respondents’ educational background in science and foreign language. The results of the study indicated that coursework in sciences at the college level, and a major in a science-related field, were the most significant predictors of the respondents’ ability to accurately define the scientific terms. This suggests that a strong background in science coursework, in addition to the traditional journalism courses, may provide the foundation that allows communicators to translate science-based information to the general public.